Comparison of ondansetron and tramadol for prevention of shivering in patients undergoing lower limb surgery under spinal anesthesia - Rayamajhi, Mallika; Shah, Aashish; Thapa, Puja; Amatya, Biswo Ram; Thapa, Kristi (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Shivering is a common and unpleasant phenomenon in patients undergoing spinal anesthesia that leads to several complications. The purpose of this study was to compare the incidence and severity of shivering in patients who received ondansetron and tramadol preemptively for the prevention of intra-operative shivering. Methods: A prospective, observational, comparative study was conducted on 100 patients, of both genders, aged 18 to 60 years with an American Society Anesthesiology Physical Status I or II, undergoing lower limb surgeries under spinal anesthesia. Patients were randomly assigned to two study groups, ondansetron (Group ON) or tramadol (Group TM) according to the medication they received 30 minutes before spinal anesthesia. The incidence of peri-operative shivering, grades of shivering, skin temperature changes and adverse effects were observed. Results: Group TM had significantly less shivering than Group ON. In group ON, 37.5% had grade 1, 8.3% grade 2, and 4.1% grade 3 shivering. Group TM had 14.8% grade 1, with no higher-grade shivering. The difference in intensity was also significant. A significant drop in axillary temperature was observed at 75 and 90 minutes post spinal anesthesia. Complications were significantly higher in Group TM, with 25 patients experiencing nausea, vomiting, or sedation, compared to just one patient in Group ON. Conclusions: Tramadol was more effective than ondansetron in preventing intraoperative shivering, however, Ondansetron was better tolerated with lower incidence of nausea and vomiting.